Water-assisted purification during electron beam-induced deposition of platinum and gold - Glessi, Cristiano; Polman, Fabian A.; Hagen, Cornelis W. (Beilstein Journal of Nanotechnology, 2024)
Direct fabrication of pure metallic nanostructures is one of the main aims of focused electron beam-induced deposition (FEBID). It was recently achieved for gold deposits by the co-injection of a water precursor and the gold precursor Au(tfac)Me2. In this work results are reported, using the same approach, on a different gold precursor, Au(acac)Me2, as well as the frequently used platinum precursor MeCpPtMe3. As a water precursor MgSO4·7H2O was used. The purification during deposition led to a decrease of the carbon-to-gold ratio (in atom %) from 2.8 to 0.5 and a decrease of the carbon-to-platinum ratio (in atom %) from 6–7 to 0.2. The purification was done in a regular scanning electron microscope using commercially available components and chemicals, which paves the way for a broader application of direct etching-assisted FEBID to obtain pure metallic structures.
Keywords: FEBID; gold; nanofabrication; platinum; purification